ANALISIS AKUISISI PERUSAHAAN TERHADAP KINERJA KEUANGAN - Rinda Ayu Kurnia (Universitas Gajayana Malang, 2020)
Companies must have efficient financial performance to be considered as a healthy company. The purpose of this research is to know the comparison of company’s financial performance before and after acquisition by using financial ratio analysis. The object of this research is PT XL Axiata Tbk company by using secondary data of book year 2012-2016. Where the new company made the acquisition in 2014. The results of this study indicate that the performance of PT XL Axiata Tbk in 2012-2013 better than 2015-2016. While in the year of acquisition in 2014 showed a negative financial performance.